Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

6j^2-2j-9=0 I need help now

Sagot :

Answer:

6j^2 - 2j = 9

j^2 -(2/6)j = 9/6

j^2 - (2/6)j + 1/36 = 9/6 + 1 /36

(j - 1/6)^2 = 55/36

j - 1/6 = √55/36

j = (√55/36) + 1/6

j = 1.40

Step-by-step explanation:

step 1 transpose 9 and it becomes positive.

step two divide everything by 6 so that j^2 has a coefficient of 1.

step 3 make a perfect square.

Then it's just simple calculations to get the answer

We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.